Determinants of Malnutrition among the Children under 2 Years of Age - Niger, Mst. Tamanna; Khatun, Shafia; Sultana, Marufa; Islam, Nurul; Kazuhiro, Ohtani (Pakistan Journal of Nutrition, 2009)
Two hundred and twenty five mothers of Dhaka medical college hospital are interviewed to investigate of determinants of malnutrition. All of our respondents were under two years of age. One hundred fourteen of them were girls and rests 111 were boys. All of the children were from different socio-economic status coming different places of Bangladesh. 28% of the respondents family monthly income were below 3001-5000, 3.6% were below 20,000-25,000 and 16.4% were 10,000-15,000, 21.3% respondents mothers were illiterate, 24.4% mothers were primary level, 32% mothers were secondary level, 11.1% mothers were higher secondary level and 11.1% were graduate. The nutritional status children were not found very from normal to 3rd degree malnourishment. Nearly 45.8% were normal, 1.8% was over nourished and 2.2% were 3rd degree malnourished. In the above context, it can be concluded that a large number of the population of Bangladeshi children are suffering from malnutrition (more than half) and are likely to grow smaller and smaller. This is implication of the fact that we are heading towards a nation that will see its children to be of small status and low weight population. So, we need to give highest priority to child health and nutrition if we hope for a brighter future of our country.